2015
DOI: 10.3354/meps11069
|View full text |Cite
|
Sign up to set email alerts
|

Local population structure and context-dependent isolation by distance in a large coastal shark

Abstract: Genetic diversity, population genetic structure and isolation by distance (IBD) were assessed in a viviparous coastal shark (the lemon shark Negaprion brevirostris) across 8 western Atlantic samples spaced between ~150 and 7000 km apart. Juveniles (N = 325) were sequenced at 2 mitochondrial loci (1729 bp) and typed at 9 nuclear encoded microsatellite loci. Analysis of mitochondrial sequences revealed higher diversity at low-latitude island samples compared to highlatitude continental samples, consistent with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 50 publications
4
34
0
Order By: Relevance
“…This is concordant with the maximum distances travelled by tagged individuals ranging between 1000 and 2000 km in the western North Atlantic and Gulf of Mexico, and with no trans‐equatorial movements being detected (Kohler, Casey, & Turner, ). The same isolation of western North Atlantic and western South Atlantic populations at mitochondrial markers also occurred in large coastal shark species such as Sphyrna lewini (Griffith & Smith, 1834); (Chapman, Pinhal, & Shivji, ), Carcharhinus leucas (Müller & Henle, 1839) (Karl et al, ), G. cirratum (Karl et al, ), Negaprion brevirostris (Poey, 1868) (Ashe et al, ), and the semi‐oceanic C. falciformis (Domingues et al, ), but not in epipelagic, oceanic shark species such as Pseudocarcharias kamoharai (Matsubara, 1937) and Carcharhinus longimanus (Poey, 1861) (Camargo et al, ; Ferrette et al, ). Individual based mtCR analyses support an isolation‐by‐distance pattern rather than the complete isolation of populations in night sharks, similar to findings for other shark species such as Carcharhinus melanopterus (Quoy & Gaimard, 1824) (Vignaud, Clua, Mourier, Maynard, & Planes, ), Sphyrna tiburo (Linnaeus, 1758) (Portnoy et al, ), and N. brevirostris (Ashe et al, ).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…This is concordant with the maximum distances travelled by tagged individuals ranging between 1000 and 2000 km in the western North Atlantic and Gulf of Mexico, and with no trans‐equatorial movements being detected (Kohler, Casey, & Turner, ). The same isolation of western North Atlantic and western South Atlantic populations at mitochondrial markers also occurred in large coastal shark species such as Sphyrna lewini (Griffith & Smith, 1834); (Chapman, Pinhal, & Shivji, ), Carcharhinus leucas (Müller & Henle, 1839) (Karl et al, ), G. cirratum (Karl et al, ), Negaprion brevirostris (Poey, 1868) (Ashe et al, ), and the semi‐oceanic C. falciformis (Domingues et al, ), but not in epipelagic, oceanic shark species such as Pseudocarcharias kamoharai (Matsubara, 1937) and Carcharhinus longimanus (Poey, 1861) (Camargo et al, ; Ferrette et al, ). Individual based mtCR analyses support an isolation‐by‐distance pattern rather than the complete isolation of populations in night sharks, similar to findings for other shark species such as Carcharhinus melanopterus (Quoy & Gaimard, 1824) (Vignaud, Clua, Mourier, Maynard, & Planes, ), Sphyrna tiburo (Linnaeus, 1758) (Portnoy et al, ), and N. brevirostris (Ashe et al, ).…”
Section: Discussionmentioning
confidence: 82%
“…Alvarado Bremer, Viñas, Mejuto, Ely, & Plas, ; Domingues et al, ; Martinez, González, Castilho, & Zardoya, ; Portnoy et al, ). The presence of two sympatric clades composed of representatives’ samples from all populations could be attributed to their recent isolation, which mitochondrial frequencies have not yet homogenized, as has been observed in other shark species (Ashe et al, ; Domingues et al, ; Portnoy et al, ).…”
Section: Discussionmentioning
confidence: 86%
“…Future studies should explore genetic differentiation by examining haplotype frequency of young of the year great hammerheads and adults sampled throughout the region. This will be important in determining if females are returning faithfully to parturition sites and whether there is an absence of female-mediated gene flow, which has consequences for stock management as discussed for other marine species, including sharks Ashe et al, 2015) cetaceans (Baker et al, 2013) and pinnipeds (Lopes et al, 2015).…”
Section: Regional Movements and Return-migrationsmentioning
confidence: 99%
“…For instance, when considering fish with a Mediterranean–Atlantic distribution, a weak differentiation is often found when comparing populations sampled at thousands of kilometres of distance (i.e., Milano et al, ; Souche et al, ), and extreme differences are found at most across major biogeographic/oceanographic transitions (Patarnello, Volckaert, & Castilho, and references therein). Indeed, for marine fish, F ST values rarely exceed 0.1–0.15 within the Mediterranean Sea, even when considering species with a limited PLD, fragmented habitat and endemism level (Astolfi et al, ; Carreras et al, ; Carreras‐Carbonell, Macpherson, & Pascual, ; Congiu et al, ), and only raise to high values when considering sharks (Ashe et al, ), reptiles (Sethuraman et al, ) and some marine mammals (Fruet et al, ). Similar pictures of low differentiation are common in several benthic invertebrates, such as sponges ( Scopalina lophyropoda , Blanquer & Uriz, ), sea urchins ( Paracentrotus lividus , Maltagliati, Di Giuseppe, Barbieri, Castelli, & Dini, , Penant, Aurelle, Feral, & Chenuil, ), sea cucumbers ( Holothuria mammata , Borrero‐Pérez, Gonzàlez‐Wanguemert, Marcos, & Pérez‐Ruzafa, ), bivalves ( Pinna nobilis , Sanna et al, ) and crustaceans ( Liocarcinus depurator , Pascual et al, ; Carcinus aestuarii , Schiavina, Marino, Zane, & Melìa, ; Pachygrapsus marmoratus , Fratini et al, ).…”
Section: Discussionmentioning
confidence: 99%